PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA ARAB DI SEKOLAH MENENGAH DI SMA AL CHASANAH JAKARTA BARAT - Muhtadin; sholahudin (LP2M JAMIAT KHEIR, 2025)
This study aims to explore the role of Islamic Education (PAI) teachers in increasing students' motivation to learn Arabic at SMA Al Chasanah, West Jakarta. The research is based on the low student interest in Arabic, often due to perceptions of the subject being difficult and less relevant, and the lack of engaging teaching approaches. This is a qualitative study using a descriptive narrative method. Data were collected through interviews, observations, and documentation involving PAI teachers and students. Findings reveal that PAI teachers play a significant role as motivators and facilitators. They not only deliver content but also instill religious values and a love for the Arabic language through spiritual and contextual approaches. Strategies include integrating Arabic into religious activities, using engaging media, and providing exemplary behavior. The study concludes that PAI teachers have a strategic role in fostering a religious and supportive learning environment, which effectively boosts students’ motivation to study Arabic.